Investigating Risk Characteristics and Dynamic Connectedness among Traditional and Modern Investments during Crises - Dimitriadis, Konstantinos (My University, 2024)
This PhD thesis examines the risk-return characteristics and dynamic interconnection of a diverse group of modern financial instruments. Such investments include 'environmentally friendly' stocks, which are vulnerable to systemic risk and the impact of non-normal distributions. Furthermore, well-known financial instruments such as gold, oil, and sectoral stock indices are examined, as well as emergingly popular investments such as wheat. Notably, this thesis focuses not only on highly innovative digital investment tools such as cryptocurrencies, but also on the most modern forms of digital assets, such as 'environmentally-friendly' cryptocurrencies, which are considered riskier but have the potential to become the most appealing to investors in the medium to long term. Diversification or hedging against higher systemic risk through the optimal synthesis of portfolios based on a thorough assessment of risk-adjusted performance dynamics may be a valuable tool for investors during crises such as the Covid-19 or the Russia-Ukraine conflict.
Keywords: Market crash price risk; Dynamic connectedness; Hedging; Traditional and modern investments; Environmentally-friendly character